Using digital inpainting to estimate incident light intensity for the calculation of red blood cell oxygen saturation from microscopy images. Issue 11 (28th June 2018) - Sové, Richard J.; Drakos, Nicole E.; Fraser, Graham M.; Ellis, Christopher G.
Abstract : Red blood cell oxygen saturation (SO2 ) is an important indicator of oxygen supply to tissues in the body. SO2 can be measured by taking advantage of spectroscopic properties of hemoglobin. When this technique is applied to transmission microscopy, the calculation of saturation requires determination of incident light intensity at each pixel occupied by the red blood cell; this value is often approximated from a sequence of images as the maximum intensity over time. This method often fails when the red blood cells are moving too slowly, or if hematocrit is too large since there is not a large enough gap between the cells to accurately calculate the incident intensity value. A new method of approximating incident light intensity is proposed using digital inpainting. This novel approach estimates incident light intensity with an average percent error of approximately 3%, which exceeds the accuracy of the maximum intensity‐based method in most cases. The error in incident light intensity corresponds to a maximum error of approximately 2% saturation. Therefore, though this new method is computationally more demanding than the traditional technique, it can be used in cases where the maximum intensity‐based method fails (eg, stationary cells), or when higher accuracy is required. Abstract : This study presents a novel use of digital image inpainting to estimate the intensity of light incident on red blood cells in intravital microscopy images to calculate red blood cell hemoglobin oxygen saturation. The new approach allows for the saturation measurement of stationary cells, which could not be accomplished with the traditional video‐based approach.